Upaya Mencegah Wabah Travel Disease dalam Persepsi Travel Agent - Harpiana Rahman; Sartika Sartika (FORIKES, 2022)
Travel agents as travel consultants play a function not only in planning travel trips, but also in preventing the transmission of COVID-19 disease in the tourism sector. However, there was no socialization related to the potential for transmission of other travel diseases such as foodborne disease, airborne disease, zoonotic disease which also threatens tourists and public health. This study aims to explore the perceptions of travel agents regarding the threat of travel disease outbreaks based on disease prevention efforts carried out by travel agents in preventing the spread of disease. The research used a qualitative approach. Primary data collection was carried out by in-depth interviews and observation of health promotion content on social media. The selection of informants was done by purposive sampling technique. The results show that the perception of travel agents affects disease prevention efforts. Travel agents did not understand about the threat from other travel diseases. It is recommended that travel associations, the health office and the tourism office intervene knowledge through training and tourism health education to travel agents so that health promotion can include controlling diseases that arise due to tourism activities, not just COVID-19Keywords: travel disease; travel agents; perception; health promotion; COVID-19; tourism health ABSTRAK Agen travel selaku konsultan perjalanan wisata, memerankan fungsi bukan hanya melakukan perencanaan perjalanan wisata, namun juga turut melakukan pencegahan penularan penyakit COVID-19 di bidang pariwisata. Namun, tidak ditemukan sosialisasi terkait potensi penularan travel disease lainnya seperti foodborne disease, airborne disease, zoonosis disease yang turut mengancam wisatawan dan kesehatan masyarakat. Penelitian ini bertujuan untuk menggali persepsi agen travel terkait ancaman wabah travel disease berdasarkan upaya pencegahan penyakit yang dilakukan agen travel dalam pencegahan penuluran penyakit. Penelitian menggunakan pendekatan kualitatif. Pengumpulan data primer dilakukan dengan wawancara mendalam dan observasi konten promosi kesehatan di media sosial. Pemilihan informan dilakukan dengan teknik purposive sampling. Hasil penelitian menunjukkan bahwa persepsi agen travel mempengaruhi upaya pencegahan penyakit. Agen travel belum memahami tentang ancaman dari travel disease lainnya. Disarankan agar asosiasi travel, dinas Kesehatan dan dinas pariwisata melakukan intervensi pengetahuan melalui pelatihan dan pendidikan kesehatan pariwisata kepada agen travel sehingga promosi kesehatan bisa mencakup pengendalian penyakit yang timbul akibat aktivitas wisata, bukan hanya COVID-19Kata kunci: travel disease; agen travel; persepsi; promosi kesehatan; COVID-19; kesehatan pariwisata